Facial discoid dermatosis in childhood. A report of two cases. - Alarcón-Pérez, C.E.; Alòs-Hernandez, L.; Baselga-Torres, E. (European Journal of Pediatric Dermatology, 2024)
Facial discoid dermatosis is a condition recently described in the literature, especially in women in the second to fourth decade of life. More than by its morphology, which is nonspecific, it is clinically characterized by its persistence and resistance to therapy. Laboratory tests and histology exclude tinea faciei, discoid lupus erythematosus, Jessner lymphocytic infiltration, eczema, leishmaniasis. The histological picture is reminiscent of pityriasis rubra pilaris, so much so that it is hypothesized that it is a new type of this disease. In the current work, two children with lesions compatible with the diagnosis of discoid facial dermatosis are described for the first time in the literature.